PENGARUH GAYA KEPEMIMPINAN DAN REMUNERASI MELALUI DISIPLIN KERJA TERHADAP KINERJA APARATUR SIPIL NEGARA DI POLITEKNIK PELAYARAN SURABAYA - Ramayana, Agus; Wibowo, Nugroho Mardi (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2024)
The purpose of this research is to find out and analyze the influence of leadership style and remuneration through work discipline on the performance of the state civil apparatus in Surabaya Merchant Marine Polytechnic. The variables used in this study are leadership style and remuneration as independent variables, work discipline as intervening variables, performance as the dependent variable. This research was conducted using data from the State Civil Apparatus in Surabaya Merchant Marine Polytechnic with a total sample of 52 employees. The test results show that Leadership Style has a positive and significant effect on Work Discipline, Remuneration has a positive and significant effect on Work Discipline, Leadership Style has a positive and significant effect on employee performance, Remuneration has a positive and significant effect on Employee Performance, Work Discipline has a positive and significant effect on Performance Employee While the leadership style does not significantly influence performance through work discipline and remuneration does not significantly influence performance through work discipline.